Design and Properties of Renewable Bioasphalt for Flexible Pavement. (2017) - Djumari,; Yami, Mujib Abdel Daim; Nasution, Muhamad Fachri; Setyawan, Ary
Abstract: In the construction world, most flexible pavement constructions use synthetic asphalt made from crude oil and well-known as conventional asphalt. Therefore, to find more environmentally friendly construction people around the world are very interested in finding a bioasphalt. The bioasphalt is used because of several reasons, such as asphalt mixtures derived from plants and trees could replace petroleum-based mixtures. One of bioasphalt which can be used as an alternative material of conventional asphalt is resin ( damar ). The existence of damar in Indonesia is very huge, especially in Lampung, South Sumatera, Indonesia. In this study, the researchers used experimental research based on laboratory works. The percentages of natural resin used in the conventional asphalt 60/70 pen are 0%, 2.5%, 5%, 7.5% and 10% modification. The selected test, including Marshall stability test to get the optimum bitumen content, unconfined compressive test, indirect tensile test and permeability test. The research result shows that asphalt with resin is different with conventional asphalt 60/70 pen in terms of asphalt quality, because the asphalt modified with resin has higher penetration value and specific gravity than conventional asphalt. The result of the Marshall stability test, unconfined compressive test, indirect tensile test and permeability test is high if the asphalt modified with higher natural resin. On the other hand, the optimum bitumen content value relatively similar with the modification of natural resin.